PEMBINAAN MENGENAI ANCAMAN KEJAHATAN CYBER DI SMK MANAGEMENT TRAINING SYSTEM BATAM - Svinarky, Irene; Silalahi, Mesri; Ukas, Ukas; Pintubipar Saragih , Saut (ASOSIASI IDEBAHASA KEPRI, 2024)
Data and information security which is currently increasingly important has resulted in many parties making efforts to control data and information at a better level, including data and information owned by students at SMK Management Training System Batam, community service activities targeted schools that are carried out will provide guidance to students and students in the school to improve expertise in securing data And personal information in order not to misuse so as to harm participants in the development of laws related to information and telecommunications technology or ITE will also be provided to increase awareness of students or all participants in using internet-based platforms. Data and information security that is currently increasingly important m Increasing the ability of participants in aspects of information technology and coupled with legal awareness in digital literacy brackets and legal literacy allows participants to have the ability to avoid mistakes and increase expertise in the use of platforms and the internet. The target of this activity is to reduce the misuse of data and information and violations of the law committed in activities related to digital platforms or the internet resulting in many